Evaluation of Parameters in PLA and PCL Scaffolds to be Used in Cartilaginous Tissues - Cea, Klear; Donoso, Marcelo; Sérandour, Guillaume; Martínez, Gabriela; Alegría, Luz (Revista Mexicana de Ingenieria Biomedica, 2021)
The scopes of medical treatments involving organ transplants and implants for chronic problems and trauma have changed significantly. However, these procedures are subject to multiple problems. Recently, tissue engineering has been used to address them. The present study is framed in the field of tissue engineering, particularly cartilage tissue, and proposes the evaluation of geometric and impression parameters for the manufacture of scaffolds as a basis for the growth of cells through 3D impression techniques. These scaffolds are highly porous three-dimensional supports that house donated or himself patient cells, providing a surface where the cells can adhere and proliferate. In the methodology, geometric and pore size variables are defined for scaffolding modeling by using CAD techniques and standardization of the printing process with standard 3D printers and accessible materials. The results showed that material flow, printing temperature, printing speed and ventilation are the most influential parameters in the manufacture of scaffolds. Additionally, it was found micrometric variations between the modeled design and the printing result. These scaffolds will subsequently be subjected to in vitro cell culture evaluating the adherence, division, and proliferation of the cells.